Accuracy of biometric formulae for intraocular lens power calculation in a teaching hospital - Kevin S Tang; Elaine M Tran; Allison J Chen; David R Rivera; Jorge J Rivera; Paul B Greenberg (International Journal of Ophthalmology, 2020)
AIM: To evaluate the accuracy of three commonly used biometric formulae across different axial lengths (ALs) at one United States Veterans Affairs teaching hospital. METHODS: A retrospective chart review was conducted from November 2013 to May 2018. One eye of each patient who underwent cataract surgery with a monofocal intraocular lens (IOL) was included. The range of postoperative follow-up period was from 3wk to 4mo. The Holladay 2, Barrett Universal II, and Hill-Radial Basis Function (Hill-RBF) formulae were used to predict the postoperative refraction for all cataract surgeries. For each formula, we calculated the prediction errors [including mean absolute prediction error (MAE)] and the percentage of eyes within ±0.25 diopter (D) and ±0.5 D of predicted refraction. We performed subgroup analyses for short (AL<22.0 mm), medium (AL 22.0-25.0 mm), and long eyes (AL>25.0 mm). RESULTS: A total of 1131 patients were screened, and 909 met the inclusion criteria. Resident ophthalmologists were the primary surgeons in 710 (78.1%) cases. We found no statistically significant difference in predictive accuracy among the three formulae over the entire AL range or in the short, medium, and long eye subgroups. Across the entire AL range, the Hill-RBF formula resulted in the lowest MAE (0.384 D) and the highest percentage of eyes with postoperative refraction within ±0.25 D (42.7%) and ±0.5 D (75.5%) of predicted. All three formulae had the highest MAEs (>0.5 D) and lowest percentage within ±0.5 D of predicted refraction (<55%) in short eyes. CONCLUSION: In cataract surgery patients at our teaching hospital, three commonly used biometric formulae demonstrate similar refractive accuracy across all ALs. Short eyes pose the greatest challenge to predicting postoperative refractive error.